Design, synthesis and biological evaluation of novel 4, 5-dihydro-[1, 2, 4]triazolo[4, 3-f]pteridine derivatives as potential BRD4 inhibitors. Issue 13 (1st July 2019) - Bi, Xinzhou; Li, Jieming; Li, Jiuhui; Shi, Wei; Dai, Yuxuan; Li, Qifei; Zhang, Wenjie; Huang, Wenlong; Qian, Hai; Jiang, Cheng
Graphical abstract: Abstract: Recently, diverse kinase inhibitors were reported having interaction with BRD4. It provided a strategy for developing a new structural framework for the next-generation BRD4-selective inhibitors. Starting from PLK1 kinase inhibitor BI-2536, we designed 18 compounds by modifying dihydropteridine core. Compound23 showed potent BRD4 inhibitory activities with IC50 of 79 nM and no inhibitory activities for PLK1. Cell antiproliferation assay was performed and potent inhibitory activity against MV4;11 with IC50 of 1.53 μM. Cell apoptosis and western blotting indicated compound23 induced apoptosis by down-regulating c-Myc. These novel selective BRD4 inhibitors provided new lead compounds for further drug development.